Characterizing soil macroporosity by X-ray microfocus computed tomography and quantification of the coring damages. - Caner L.; Sardini P.; Robinet J.C.; Hubert F.; Gallier J. (EPJ Web of Conferences, 2010)
X-ray Computed Tomography (X-ray µCT) was employed to characterize vertical variations of structural porosity of a soil profile (pore dimension higher than 5.103 µm3). Three distinct horizons of a Cambisol have been studied for a total depth of 75 cm: L, S1/S2 and S2/SFe horizons. Samples have been cored in situ by driving in PVC tubes (inner diameter 10 cm). From reconstructed and filtered volumes, pores segmentation allows to study variations of structural porosity within the profile. Two kinds of porosity were identified: biological pores (tube-like) and physical pores (fracture-like). Structural porosity content varies strongly according to the horizons: from 5.48% in the L horizon to 6.48% in the S1/S2 horizon. The 3D connectivity of both of these pore types was also assessed. During sampling, soil shearing induced damages around the cores. Identification and quantification of the damaged zone was performed from the calculation of porosity profile from core surface to core heart. In average, the damaged zone reaches a depth of 1 cm. Porosity loss (compaction) or porosity increase (fracturing) was observed according to the studied profile.